Evaluating the Trend of Changes in Groundwater Quality Parameters (Case Study: Jiroft Plain) - Soleimani Sardoo, Farshad; Azareh, Ali (European Journal of Sustainable Development, 2017)
In recent decades, population growth and development of agriculture, indiscriminate increase and exacerbate the decline in the quality of groundwater resources in most parts of the country. Thus, given the importance of this research to study the spatial and temporal changes in parameters of calcium, magnesium, pH, chloride, sodium sulfate and water in Jiroft discussed. The data from 40 wells in the region of Kerman province in 2002 - 2012 water harvesting and qualitative analysis had been done on it was used. In this regard, after normalizing the data to evaluate the accuracy of different geostatistical methods including the kriging and inverse distance weighted, and then map the spatial zoning in the software quality parameters ArcGIS9.3 was prepared using the best method of interpolation. The results showed that the amount of calcium, pH and chlorine in the water and magnesium, and sodium sulfate also has declined. But the quality of groundwater resources Jiroft in general in 2012 compared to 2002, decreased and the process of change if they do go to the South and West Water quality is reduced. Keyword: Modeling, Jiroft plains, groundwater, spatial changes, interpolation.